Relevance of Helicobacter pylori virulence factors for vaccine development Relevancia de los factores de virulencia de helicobacter pylori para el desarrollo de vacunas - Luz del Carmen Hernández-Hernández; Eduardo César Lazcano-Ponce; Yolanda López-Vidal; Germán Rubén Aguilar-Gutiérrez (Instituto Nacional de Salud Pública, 2009)
Helicobacter pylori infection increases the risk for a wide spectrum of clinical outcomes, ranging from peptic ulcer disease to gastric cancer. However, the infection induces gastric and duodenal ulceration or gastric cancer in only a minority of infected subjects because H. pylori strains are genetically diverse and express different virulence factors. Individuals infected with strains that express these virulence factors probably develop severe diseases such as gastric cancer. Nevertheless, the ancient relationship between H. pylori and humans suggests that some strains could be beneficial to human health, which means that generalized administration of antibiotic therapy could eventually cause problems. The development of vaccines based on virulence factors that provide long-term protection is the best strategy for control and/or elimination of pathogenic strains. The different immunization schemes and formulations designed to evaluate the vaccines based on virulence factors in animal models have offered promising results. However, it is necessary to determine whether or not these results can be reproduced in humans. This article reviews recent vaccination studies that explore this possibility: oral vaccines using urease or inactivated whole cells plus LT as adjuvant and urease expressed in Salmonella spp. vectors, as well as a parenteral multicomponent vaccine plus aluminum hydroxide as adjuvant. Although these studies have achieved limited success, they have established support for the development of an effective vaccine against this infection. La infección por Helicobacter pylori incrementa el riesgo de un amplio espectro de cuadros clínicos, que van de la úlcera péptica al cáncer gástrico. Sin embargo, la infección sólo induce ulceración gástrica y duodenal o cáncer gástrico en la minoría de los sujetos infectados debido que las cepas de H. pylori son genéticamente diversas y expresan diferentes factores de virulencia. Así, los individuos infectados por cepas que expresan estos factores de virulencia probablemente desarrollan enfermedades severas como el cáncer gástrico. Sin embargo, la ancestral relación entre H. pylori y los humanos sugiere que algunas cepas pueden ser beneficiosas para la salud humana. Por lo tanto, la administración generalizada de tratamientos con antibiótico podría eventualmente causar problemas. El desarrollo de vacunas con base en factores de virulencia que confieran protección a largo plazo es la mejor estrategia para el control y/o eliminación de cepas patógenas. Los diferentes esquemas y formulaciones de inmunización diseñados para evaluar las vacunas con base en factores de virulencia en modelos animales han dado resultados prometedores. Sin embargo, ha sido necesario probar si estos resultados pueden ser reproducidos en humanos. Este trabajo revisa los recientes estudios de vacunación que han explorado esta posibilidad: vacunas orales usando ureasa o células completas-inactivadas con LT como adyuvante y ureasa expresada en vectores de Salmonella spp.; además de una vacuna intramuscular multicomponente con hidróxido de aluminio como adyuvante. Aunque estos estudios han logrado limitado éxito han establecido las bases para el desarrollo de una vacuna eficaz contra esta infección.